Investigation of Oral Health Awareness and Associated Factors Among Japanese University Students: Analyzing Behaviors Influencing Lifelong Oral Health Promotion - Yamamoto, Tsukasa; Seguchi, Manato; Mori, Yukihiro; Ejiri, Harumi; Tanaka, Mamoru; Kozai, Hana; Iio, Yoko; Aoyama, Yuka; Ito, Morihiro (Healthcare (Basel), 2025)
Background: University students’ awareness of oral health plays an important role in lifelong health promotion. However, the factors influencing this awareness among Japanese university students are not fully understood. This study aimed to comprehensively examine and analyze Japanese university students’ perceptions of their oral health status, self-reported oral symptoms, and oral health-related behaviors. Methods: A cross-sectional survey was conducted among undergraduate students using an anonymous online questionnaire to collect information on their basic attributes and self-reported items related to oral health status, oral health behavior, and lifestyle habits. The chi-square test and logistic regression analysis were used to examine factors associated with oral health status. Results: A total of 5482 students participated in this study. Overall, 75.9% of the respondents reported that their oral health was good. Factors significantly associated with good oral health were the absence of dental caries and periodontal disease, tooth brushing at least twice a day, regular dental visits, conscious toothpaste selection, and lack of concern about dental care costs and pain during treatment. Conclusions: Oral diseases and symptoms, oral health behaviors, and psychosocial factors were strongly associated with university students’ awareness of their oral health. Since oral health is closely related to systemic health, it is essential to promote proper oral hygiene practices at an early age. Therefore, providing oral health education for university students may contribute to lifelong health promotion and prevention of systemic diseases.